PERANCANGAN USER INTERFACE APLIKASI BERBASIS WEB HIMPUNAN MAHASISWA INFORMATIKA MENGGUNAKAN METODE GOAL DIRECTED DESIGN - Aros , Desfi Silvia; Budiman (Universitas Majalengka, 2025)
Communication between students and student associations often encounters obstacles, especially in conveying criticism and suggestions openly due to psychological factors and media limitations. This results in a lack of active student participation in conveying aspirations that should be used as material for organizational evaluation and improvement. This study aims to design a web-based user interface for the Informatics Student Association organizational information system that supports the delivery of informatics student aspirations through anonymous feedback features and the integration of an Artificial Intelligence (AI)-based chatbot to provide initial responses to student questions. The system design method was built using the Goal Directed Design (GDD) Method. The results of this study are expected to be a system that can be built and implemented to facilitate two-way communication more effectively, provide a safe space for students to convey criticism and suggestions, and assist the organization in managing information in a more structured manner. With this system, the level of student participation in conveying aspirations can be increased, and the organization obtains more relevant data for decision-making and evaluation of organizational performance.